Pengaruh Karakter, Motivasi, dan Lingkungan Belajar terhadap Kemampuan Berpikir Kreatif Siswa Kelas VIII dalam Perspektif Ekologis pada Pembelajaran Bahasa Indonesia - Etty Umamy; Indria Kristiawan; Khoirul Efendiy (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to examine the influence of character, motivation, and learning environment on the creative thinking ability of eighth-grade students in Indonesian Language lessons at SMP Negeri 1 Jabung and SMP Negeri 1 Pakis, Malang Regency. Based on Bronfenbrenner's ecological theory (1979), which emphasizes the role of the learning environment, this research uses a quantitative approach with a descriptive correlational design, involving 231 students selected as samples using the Raosoft method. Data were collected through questionnaires and creative thinking tests, which were tested for validity and reliability. The analysis results indicate that students' character significantly influences creative thinking ability (t-statistic = 4.133, coefficient = 0.242), where positive character traits such as discipline and responsibility support creativity. Learning motivation also has a significant effect (t-statistic = 5.973, coefficient = 0.368), with intrinsic motivation playing a dominant role in enhancing creativity. Additionally, a conducive learning environment (t-statistic = 3.502, coefficient = 0.199) also supports the development of students' creativity. These findings emphasize the importance of developing character, motivation, and the learning environment to create conditions that foster student creativity, contributing to better educational policies.